Variations of bile duct confluence: uncommon risk factor for hilar cholagiocarcinoma? - M. A. Shorikov; O. N. Sergeeva; D. Yu. Frantsev; M. G. Lapteva; I. D. Reshetarov; E. A. Moroz; A. V. Kukushkin; Е. R. Virshke; B. I. Dolgushin (Сибирский онкологический журнал, 2020)
The purpose of the study was to assess the frequency of bile duct confluence variations in patients with hilar cholangiocarcinoma and in patients with no biliary lesions.Material and Methods. The study included 203 patients with Klatskin tumor (study group) and 191patients having no bile duct lesions (control group). All patients underwent abdominal MRI including MR-cholangiopancreatography. In addition, 141 patients from the study group underwent percutaneous transhepatic cholangiography. Anatomic variations of the bile duct confluence were based on Nakamura classification.Results. In the study group, type I, II, III, IV and V confluences were detected in 27.6 %, 22.2 %, 1.5 %, 36.0 % and 2.4 % of cases, respectively. In the control group, the frequencies of each type of the bile duct confluence were as follows: type I in 75.0 %, type II in 9.3 %, type III in 0.5 %, type IV in 14.2 % and type V in 1.0 %. Differences between groups were statistically significant (p<0.001). Statistical and hydrodynamic bile duct confluence models that could explain the differences between the groups were proposed.Conclusion. The frequency of uncommon bile duct confluences in patients with Klatskin tumor was significantly higher than that observed in patients having no biliary lesions; it might be due to a larger area of bile ducts in non-first confluence types or higher endobiliary pressure.